Pengaruh Terapi Islam Dalam Kegiatan Fatihahan Terhadap Peningkatan Self Management Pada Santri Di Pondok Pesantren Mahasiswa Al-Jihad Surabaya (Jurusan Bimbingan dan Konseling Islam, 2020)
This study aims to find out how much influence the Islamic therapy by fatihahan activities to improve self management of Al-Jihad Islamic Boarding School students (santri) in Surabaya, and to find out the level of Islamic therapy by fatihahan activities to improve the students' self management. Quasi Experimental Design with Wilcoxon Matches Pairs Test analysis was used. There were four determined indicators, namely low self-management students, students who have job, and students who are often late, senior students. The influence level of fatihahan activities in improving self management of the students can be seen from the comparison of pre test and post test score. The results were higher in post test score (z values of -1.826 and the p value of 0.068). It can be concluded that Islamic therapy in fatihahan activities has an effect on improving the self-management of students at the Al-Jihad Islamic Boarding School Surabaya.